Hypereosinophilic Syndrome Masquerading as a Dialyzer Reaction: A Great Mimicker - Yusra Hashim; Siti Nur Hakimah Hashim; Kuan Yee Lim; Nur Ezzaty Mohammad Kazmin; Muhammad Yusuf Abu Shamsi; Lydia Kamaruzaman (Galenos Publishing House, 2026)
Indexed by Scopus